Cross-Point Resistive Switching Memory and Urea Sensing by Using Annealed GdOx Film in IrOx/GdOx/W Structure for Biomedical Applications. Issue 4 (1st January 2017) - Kumar, Pankaj; Maikap, Siddheswar; Ginnaram, Sreekanth; Qiu, Jian-Tai; Jana, Debanjan; Chakrabarti, Somsubhra; Samanta, Subhranu; Singh, Kanishk; Roy, Anisha; Jana, Surajit; Dutta, Mrinmoy; Chang, Ya-Ling; et al.
Abstract : Resistive switching characteristics and urea sensing have been investigated by using annealed GdOx film in IrOx /GdOx /W cross-point memory for the first time. The annealed GdOx film shows larger polycrystalline grains as compared to as-deposited films, which is observed by high-resolution transmission electron microscope (HRTEM) and X-ray diffraction patterns (XRD). Surface roughness of the GdOx films on W nano-dome is observed by atomic force microscope (AFM). The annealed IrOx /GdOx /W cross-point memory shows resistance ratio of 1000× times higher, multi-level operation with varying current compliance (CC) from 10–300 μA, good non-linearity factor of 8.3, good dc switching cycles of > 1000 at CC of 10 μA, long read endurance of >10 9 cycles with pulse width of 1 μs at higher read voltage of −0.5 V, and high speed operation of 100 ns. Repeatable resistive switching characteristics at low CC of 10 μA and mechanism are due to the electric field enhancement on the W nano-dome simulated by MATLAB, which controls the O 2− ions migration through polycrystalline GdOx grain boundary as well as Schottky barrier height modulation (0.59 vs. 0.39 eV). In addition, the annealed GdOx membrane in electrolyte-insulator-semiconductor (EIS) structure shows higher pH sensitivity than the as-deposited film (53.2 vs. 45.1 mV/pH) and lower drift (1.8 vs. 2.6 mV/hr) as well as lower detection of pH change (0.034). Detection of pH and urea sensing from 6 to 24 mg/dl have been measured by using cross-point memory, and the sensing mechanism is also discussed, which will be very useful for real healthcare unit in near future.